Moby dick - Brook, Henry; Harvey, Bob Melville, Herman (Usborne Pub Ltd; London, 2014)
A faithful retelling of the classic Herman Melville story about Captain Ahab and his vengeful hunt for the whale Moby Dick. Clearly written in a modern, approachable style, this series is designed to introduce young readers to much-loved classic stories